2009
DOI: 10.1111/j.1440-1827.2009.02355.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression of syndecan‐1 and Ki‐67 in peripheral and desmoplastic ameloblastomas and ameloblastic carcinoma

Abstract: The aims of the present study were to examine whether the pattern of syndecan-1 expression correlates with cellular proliferation index in desmoplastic ameloblastomas (DA), peripheral ameloblastomas (PA) and ameloblastic carcinomas (AC), and to compare with that previously reported for solid (SA) and unicystic (UA) variants of ameloblastoma. Immunohistochemistry was performed for syndecan-1 and Ki-67 in seven ameloblastomas (four DA and three PA) and three AC. Expression of syndecan-1 was related to the histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 33 publications
6
42
2
4
Order By: Relevance
“…Overall, however, all ameloblastomas have been shown to have a very low proliferative index (Fig. 1f, reviewed in Gomes et al [17]), and it is possible that proliferation markers may be useful to help diagnose malignant ameloblastomas, especially in small biopsies [18]. However, this issue requires further exploration to determine its clinical usefulness.…”
Section: Neoplastic Odontogenic Epitheliummentioning
confidence: 96%
“…Overall, however, all ameloblastomas have been shown to have a very low proliferative index (Fig. 1f, reviewed in Gomes et al [17]), and it is possible that proliferation markers may be useful to help diagnose malignant ameloblastomas, especially in small biopsies [18]. However, this issue requires further exploration to determine its clinical usefulness.…”
Section: Neoplastic Odontogenic Epitheliummentioning
confidence: 96%
“…Immunohistochemical expression of CK5 in basal/suprabasal cells and CK14 in suprabasal/central cells in the present case offer evidence of maturation of the epithelial component; low index of p53 protein and Ki-67 expression in epithelium and stromal cells of PDA, as well as CD138 uniform positive-stain in epithelial cells, support the benign biological behavior of the lesion, as has been reported previously in their intraosseus counterpart. (13) High expression of syndecan-1 in DA could be associated with a better cell-cell and cell-extracellular matrix adhesion in epithelial ameloblastic zones (islands), suggesting a less aggressive and invasive behavior and could explain, to some degree, the unique clinicopathological features of this slow growing lesion, which in turn, may favor the presence of desmoplasia (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that peripheral ameloblastomas may present indolent behavior compared with the central variant (10,22,23). Thus, the treatment of choice is a conservative supraperiosteal excision with adequate disease-free margins (1,4).…”
Section: Discussionmentioning
confidence: 99%